Optimized conversion of waste cooking oil to biodiesel using modified calcium oxide as catalyst via a microwave heating system. (15th April 2020) - Hsiao, Ming-Chien; Kuo, Jui-Yang; Hsieh, Shu-An; Hsieh, Pei-Hsuan; Hou, Shuhn-Shyurng
Highlights: Transesterification of waste cooking oil (WCO) to biodiesel was investigated. Synthesis of modified CaO was dramatically enhanced with a microwave reactor. Microwave-modified CaO had better thermos-stability than the convention method. Microwave radiation improved biodiesel production with modified CaO catalysts. The optimal parameters were investigated for the transesterification reaction. Abstract: Homogeneous catalysts have been commonly utilized during the production of biodiesel in industrial applications. However, a homogeneous catalysis system has several disadvantages, including difficulties related to the separation of the reactant and products and the pollution of wastewater after the chemical washing process. However, transesterification through heterogenous catalysis avoids the aforementioned drawbacks in the homogeneous catalysis process. In this study, a novel modified calcium oxide (CaO) is proposed as an alkaline solid catalyst. The surface of commercial CaO is chemically modified using bromooctane through a microwave approach to improve its catalytic ability. The physiochemical characteristics of the modified CaO are analyzed using a Fourier transform infrared (FTIR) spectrometer, X-ray diffraction (XRD), and thermogravimetric analysis (TGA). The results show that microwave heating significantly reduces the synthesis time for the modified CaO, which was found to be one twelfth that of traditional water-bath heating. In addition, calcium hydroxide (Ca(OH)2 ) was rarely generated during the modification procedure, and microwave-modified CaO was found to have better thermos-stability. The optimal reaction conditions are as follows: a 4 wt% catalyst, a methanol-to-oil molar ratio of 8:1, a reaction temperature of 65 °C, and a reaction time of 75 min. Under these conditions, the biodiesel conversion reaches 98.2%, while the reaction time (75 min) is only 53.6% of the traditional water bath heating transesterification reaction (140 min).